Combination therapy of Allium cepa L. and Cucumis sativa L. extracts in streptozotocin-induced diabetic rat model - O. M. Ighodaro; A. M. Adeosun; T. S. Ujomu; O. O. Durosinlorun; C. C. Okosa (SpringerOpen, 2021)
Abstract Background The study assessed the effects of aqueous extracts of Allium cepa, Cucumis sativa and their combined formulation (1:1) on changes in body weight, fasting blood glucose level (FBGL), pancreas morphology and serum lipid concentration in streptozotocin-induced diabetic rats. Forty-two male rats were randomly assigned to six groups: A, B, C, D, E, and F (n = 7). Except for the control animals (group A), diabetes mellitus was experimentally induced in other groups (B to F) via a single intraperitoneal injection of freshly prepared streptozotocin. Thereafter, the diabetic control animals (group B) were left untreated and other diabetic groups were treated as follows: C (Allium cepa 10 mL/kg of body weight (mL/kg BW), D (Cucumis sativa 10 mL/kg BW), E (Allium cepa and Cucumis sativa 10 mL/kg BW), and F (Metformin 12 mg/kg BW). All treatments lasted for seven days and FBGL was monitored at two days intervals. The rats were then sacrificed, and blood samples were collected for serum lipid estimation. Results Treatments of diabetic rats with Allium cepa, Cucumis sativa and their combined formulation prevented significant (P < 0.05) loss in body weight which was evident in the diabetic control counterparts. Similarly, the various treatment options curtailed the hike in blood glucose induced by streptozotocin. The hypoglycemic effect of Allium cepa was particularly notable and comparable to that of Metformin. Serum high-density lipoprotein and low-density lipoprotein-cholesterols which were significantly altered in the diabetic control animals were restored to near normal following treatments with Cucumis sativa, and its combination with Allium cepa. These observations were substantiated by the outcome of the histopathological examination of the representative pancreases. Conclusion Allium cepa appears to be more effective in blood glucose homeostasis in the diabetic animals compared to Cucumis sativa and their combined formulation. Conversely, Cucumis sativa and its combination with Allium cepa had better effects on the physiological levels of serum cholesterols in the animals. Regular consumption of Allium cepa and Cucumis sativa may be helpful in controlling blood glucose and cholesterol levels in the diabetics.